Acute Pyelonephritis in Pregnancy: A Retrospective Descriptive Hospital Based-Study. (14th November 2012) - Dawkins, J. C.; Fletcher, H. M.; Rattray, C. A.; Reid, M.; Gordon-Strachan, G.
Abstract : Introduction . Pyelonephritis is a common complication of pregnancy. It is also exacerbated by immunocompromised states and also the sickle cell gene. We reviewed this condition in Jamaican women. Method . We did a six year hospital database docket review. We found 102 confirmed cases. Results . Pyelonephritis was found in 0.7% of deliveries. The mean maternal age was 24 ± 5.83 years with 51% primiparity. Most (58.8%) occurred in the second trimester. The main symptoms were loin pain (96.2%) and abdominal pain (84.6%). It was more common on the right side in 67% of cases. On urinalysis, 81.4% had pyuria. The commonest organism was Escherichia coli, in 61% of cases. Patients given Antibiotics prior to admission had quicker resolution, P < 0.02 . Haemoglobin S was found in 16% cases (general population 10%; P = 0.002 ) . However diabetes was only found in 1.3% cases (1.5% expected). 61.3% had positive urine culture after treatment showed that 61.3% and 25% had recurrent pyelonephritis. Complications included 32% threatened preterm labour and 17% preterm delivery. About 6% of neonates had intrauterine growth restriction. There were no ICU admissions and no deaths. Conclusion . Early recognition and treatment of pyelonephritis result in good outcome. The condition is more prevalent in patients with the sickle cell gene and recurrence is high.